1977
DOI: 10.1164/arrd.1977.116.3.469
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Pulmonary Emphysema with Human Leukocyte Elastase1–3

Abstract: Purified human leukocyte elastase was injected into the tracheas of 46 hamsters. Thirteen animals died spontaneously within 1 week, with extensive lung hemorrhage. The elastin content of the lungs was only slightly less than control values 3 hours after injection. At 2 months, the lungs of the remaining animals showed mild, patchy emphysema and morphometric changes consistent with emphysema. These results contrasted with the effects of a similar elastolytic dose of pancreatic elastase administered to 26 other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
122
1
4

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(135 citation statements)
references
References 0 publications
8
122
1
4
Order By: Relevance
“…29 -31 Anti-LTB 4 serum, [5,6,8,9,11,12,14,15,3 H(N)]-LTB 4 , and synthetic LTB 4 were purchased from Amersham Co. (Arlington Heights, IL). Briefly, ethanol and supernatant mixtures were centrifuged at 5500 ϫ g at 0°C.…”
Section: And Paf In the Supernatant Fluidmentioning
confidence: 99%
See 1 more Smart Citation
“…29 -31 Anti-LTB 4 serum, [5,6,8,9,11,12,14,15,3 H(N)]-LTB 4 , and synthetic LTB 4 were purchased from Amersham Co. (Arlington Heights, IL). Briefly, ethanol and supernatant mixtures were centrifuged at 5500 ϫ g at 0°C.…”
Section: And Paf In the Supernatant Fluidmentioning
confidence: 99%
“…8 Senior and co-workers reported that experimental emphysema was induced by intratracheal instillation of purified human neutrophil elastase in animals. 9 Thus, the cigarette smoke may influence both matrix damage and repair processes, leading to lung destruction by inflammatory processes.…”
mentioning
confidence: 99%
“…Neutrophil elastase was shown to induce experimental emphysema in animals. (Senior, et al 1977). These findings lead to the first hypothesis describing the pathogenesis of lung disease, that an imbalance of proteases and anti-proteases could result in an unregulated destruction of critical components of lung structure, namely elastin, leading to the development of clinical lung disease.…”
Section: History Of the Disordermentioning
confidence: 99%
“…It may be furthermore noted from Fig. 3 that approximately 40 (20,21), it should be possible to demonstrate whether inhibitor-bearing microspheres can in fact prevent the development of emphysema without undue damage to the animal.…”
Section: Synthesis and Inhibitory Activity Of Inhibitor-bound Microspmentioning
confidence: 98%